Optimizing Empowerment, Digital Technology Literacy, Ease of Access, and Creative Economy Inclusiveness of MSME Actors: Empirical Study in Purwakarta Regency - Alviano Fidya Nugroho; Kanaya Rifhalda Putri; Ikhsan Azidan (International Forum of Researchers and Lecturers, 2024)
Objective – This research clarifies the factors that encourage creative economic inclusiveness for MSME actors by examining the effect of optimizing MSME empowerment, the role of digital technology literacy and ease of access for MSME actors. This research also examines analysis direct influence optimization empowerment on digital technology literacy and ease of access, the influence of digital technology literacy on ease of access and the mediating role of digital technology literacy and ease of access. Design/methodology/pe approach – Data was taken from an online questionnaire of respondents, namely MSME actors in Purwakarta Regency. Partial least squares structural equation modeling and mediation analysis using the bootstrap method. Findings – Optimizing empowerment and ease of access has a significant direct impact on the inclusiveness of the creative economy. Both optimizing empowerment and digital technology literacy have a direct, positive and significant influence on ease of access. Optimizing empowerment has a positive effect on digital technology literacy. Mediation analysis revealed that ease of access was unable to mediate the influence between optimizing empowerment and inclusiveness of the creative economy and between digital technology literacy and inclusiveness of the creative economy. Research limitations/implications – This research focuses on three factors that encourage creative economic inclusiveness of MSME actors in Purwakarta Regency. Originality/value – This study offers new insights into the factors that encourage the inclusiveness of the creative economy of MSME players. These findings reveal the importance of optimizing MSME empowerment and encouraging digital technology literacy for creative economic inclusivity among MSME players.